Investigation into the Effect of Altitude on the Differential Hemocyte Count of Circulating Plasmatocytes and Granulocytes of Larval Stage of Antheraea assama (Lepidoptera: Saturniidae). Issue 1 (3rd June 2015) - Baishya, Bhavna Prishnee; Bardoloi, Sunayan; Bharali, Rupjyoti
Abstract : Differential hemocyte count of circulating plasmatocytes (PL) and granulocytes (GR) of fifth-instar larvae of Muga Silkworm Antheraea assama Westwood (Lepidoptera: Saturniidae) reared at four different sericulture farms situated at different altitudes, viz, Khanapara State Sericulture Farm, Assam, altitude 55.5 m above sea level (ASL); Nongpoh (Central Silk Board farm), Meghalaya, altitude 464 m ASL; Tura (Central Silk Board farm), West Garo Hills, Meghalaya, 657 m ASL; and Kalimpong (Central Silk Board farm), West Bengal, altitude 1, 247 m ASL, were calculated and compared to investigate the effect of altitude on the number of PL and GR per mm 3 of larval hemolymph. The investigation showed that the mean circulating PL and GR were highest at Khanapara (55.5 m ASL) located at the lowest altitude, whereas their numbers gradually decreased with increase in altitude at Nongpoh (464 m ASL), Tura (657 m ASL), and Kalimpong (1, 247 m ASL). This may be attributed to the average environmental temperatures observed at different altitudes, which may affect the overall hemocyte load of larval stages reared at those altitudes.